Question
upstudy study bank question image url

Evaluate the following: \( \begin{array}{llll}\text { (a) } i^{13} & \text { (b) } 2 i^{3} & \text { (c) } i^{7} & \text { (d) } i^{14}\end{array} \)

Ask by Munoz Frank. in Nigeria
Jan 12,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( i^{13} = i \), \( 2i^{3} = -2i \), \( i^{7} = -i \), \( i^{14} = -1 \).

Solution

To evaluate the powers of the imaginary unit \( i \), we use the fact that \( i \) repeats its values every four powers: \[ i^1 = i, \quad i^2 = -1, \quad i^3 = -i, \quad i^4 = 1, \quad \text{and so on.} \] Let's evaluate each part: **(a) \( i^{13} \)** \[ 13 \div 4 = 3 \text{ with a remainder of } 1 \] So, \[ i^{13} = i^{4 \times 3 + 1} = (i^4)^3 \times i^1 = 1^3 \times i = i \] **(b) \( 2i^{3} \)** \[ i^{3} = -i \] Therefore, \[ 2i^{3} = 2 \times (-i) = -2i \] **(c) \( i^{7} \)** \[ 7 \div 4 = 1 \text{ with a remainder of } 3 \] So, \[ i^{7} = i^{4 \times 1 + 3} = (i^4)^1 \times i^3 = 1 \times (-i) = -i \] **(d) \( i^{14} \)** \[ 14 \div 4 = 3 \text{ with a remainder of } 2 \] So, \[ i^{14} = i^{4 \times 3 + 2} = (i^4)^3 \times i^2 = 1^3 \times (-1) = -1 \] **Summary of Results:** \[ \begin{align*} \text{(a) } & i^{13} = i \\ \text{(b) } & 2i^{3} = -2i \\ \text{(c) } & i^{7} = -i \\ \text{(d) } & i^{14} = -1 \\ \end{align*} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To evaluate the powers of \( i \), we first recall that \( i \) is the imaginary unit defined by the property \( i^2 = -1 \). The powers of \( i \) cycle every four terms: \[ \begin{align*} i^1 & = i, \\ i^2 & = -1, \\ i^3 & = -i, \\ i^4 & = 1, \end{align*} \] and then \( i^5 = i \), \( i^6 = -1 \), and so forth. Now, let's evaluate each term: (a) \( i^{13} \) To find \( i^{13} \), we can reduce the exponent modulo 4: \[ 13 \mod 4 = 1 \quad (\text{since } 13 = 3 \cdot 4 + 1) \] So, \( i^{13} = i^1 = i \). (b) \( 2i^{3} \) First, we evaluate \( i^3 \): \[ i^{3} = -i \] Thus, we have: \[ 2i^{3} = 2(-i) = -2i. \] (c) \( i^{7} \) To find \( i^{7} \), we reduce the exponent: \[ 7 \mod 4 = 3 \quad (\text{since } 7 = 1 \cdot 4 + 3) \] So, \( i^{7} = i^3 = -i \). (d) \( i^{14} \) For \( i^{14} \): \[ 14 \mod 4 = 2 \quad (\text{since } 14 = 3 \cdot 4 + 2) \] Thus, \( i^{14} = i^2 = -1 \). In summary, we have: - \( i^{13} = i \) - \( 2 i^{3} = -2i \) - \( i^{7} = -i \) - \( i^{14} = -1 \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy